Introduction of polyvinyl pyrrolidone (PVP) In the non surgical periotherapy of Rapidly progressive periodontitis - Al-Juboury Abdullatif; Al-Mousilly M. Maiada (College of Pharmacy / Mustansiriyah University, 2005)
The non surgical periotherepy are based on the bacteriologic back ground of periodontal diseases. More than 46 different verulant species were composing the bacterial flora. Tetracycline, doxycyline, minocyline were used systemically and / or topically in association with conventional scaling and root planning, as well chlorhexidine and wide variety of antiseptics were used. Rapidly progressive type A and type B being a complex disease showing a specific entity and a complex bacterial flora, a curative non surgical remedy not yet well realized. The polyvinyl pyrrolidone (PVP) a highly effective wide broad spectrum bactericidal, fungicidal and virocidal antiseptic used in low concentration (3%) as an intrapocket irrigation solution accompanied with conventional ultrasound scaling and root planning. Eight patients having rapidly progressive periodontal (3 of type A , 5 of type B) were involved in this study, 12 therapeutic sessions were performed during 6 months. Once a week, in the first month, twice a month in the next 3 months, then once a month in the later 2 months. The result showed a significant improvement of the clinical parameters, gingival bleeding index (GBI), clinical pocket depth (CDD) and clinical tooth mobility (CTM) and with radiologic evidences of bone formation. The result suggests that PVP could be the promising effective, safe, clinically applicable, easy to use, and cheap remedy of complex periodontal diseases.